2013
DOI: 10.1146/annurev-immunol-032712-095910
|View full text |Cite
|
Sign up to set email alerts
|

Pathways of Antigen Processing

Abstract: T cell recognition of antigen presenting cells depends on their expression of a spectrum of peptides bound to Major Histocompatibility Complex class I (MHC-I) and class II (MHC-II) molecules. Conversion of antigens from pathogens or transformed cells into MHC-I and MHC-II-bound peptides is critical for mounting protective T cell responses, and similar processing of self proteins is necessary to establish and maintain tolerance. Cells use a variety of mechanisms to acquire protein antigens, from translation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
1,135
1
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,265 publications
(1,165 citation statements)
references
References 232 publications
(225 reference statements)
18
1,135
1
11
Order By: Relevance
“…The resulting peptides are transported into the ER through the transporter associated with antigen processing (TAP), where they are loaded onto the awaiting MHC class I molecules by specialized chaperones (24)(25)(26). It is also suggested that some of the MHC peptides are produced by degradation of ER-resident proteins and their signal peptides (27,28).…”
Section: Dripome | Immunopeptidome | Dynamic Silacmentioning
confidence: 99%
“…The resulting peptides are transported into the ER through the transporter associated with antigen processing (TAP), where they are loaded onto the awaiting MHC class I molecules by specialized chaperones (24)(25)(26). It is also suggested that some of the MHC peptides are produced by degradation of ER-resident proteins and their signal peptides (27,28).…”
Section: Dripome | Immunopeptidome | Dynamic Silacmentioning
confidence: 99%
“…2 This activity involves the degradation of foreign proteins (antigens) in endo-lysosomal compartments, binding of the resulting peptides to MHC II, and delivery of the MHC II-peptide complexes to the cell surface for presentation to helper T lymphocytes. 3 Material present in endosomal compartments including plasma membrane proteins, components of the endosomal route and extracellular pathogens that are captured by endocytosis is thus readily presented via MHC II. Autophagy enables cells to expand the repertoire of antigens presented via this pathway by delivering cytosolic material to endo-lysosomal compartments, where it can be used as a source of MHC II peptide ligands.…”
Section: Introductionmentioning
confidence: 99%
“…The MHC I-peptide complexes are delivered to the plasma membrane for activation of cytotoxic T lymphocytes. 3 Cross-presentation is carried out primarily, if not only, by specific types of dendritic cells (DC). DC are highly specialized cells of the immune system that are dedicated to surveillance of the extracellular environment, the capture of pathogens and the initiation of T cell immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to immature DCs, activated DCs efficiently convert to stable expressors of newly formed pMHCII complexes at their plasma membrane to increase the chance of interaction with TCRs on CD4 þ T cells. The distinctive mechanisms and pathways for MHCI and MHCII antigen loading and trafficking have recently been compared in several excellent reviews (Neefjes et al 2011;Blum et al 2013;Mantegazza et al 2013). The present review focuses in depth on mechanisms and pathways that regulate and determine the expression of pMHCII complexes at the plasma membrane of DCs.…”
mentioning
confidence: 99%